Amor, casamento e sexualidade : a construção de identidades femininas múltiplas em Livia Garcia-Roza - Marques, Aline Cristina de Farias (2011)
This dissertation analyzes the representation and construction of multiple female identities of the characters Gilda, protagonist in female Solo (2002), and Maria, in the novel Milamor (2008), both of the contemporary writer Livia Garcia-Roza. These identities are built from the perspective of sexuality, love and marriage, placed as essential for the construction of life projects of the narrator-protagonist, which are the result of the clash between the "wanting-tohe " and "should-be". In a multidisciplinary proposal, we have relied on theoretists such as Anthony Giddens (1993), Elizabeth Badinter (c1986), Malvina Muszkat (1985, 1992), representatives of different disciplines, like sociology, philosophy, psychology, among others, which were basic to the explanation of concepts linked to changing gender relations and the new configurations of relationships from modernity. Equipped with this theoretical apparatus, it becomes apparent how the literary work of Livia Garcia-Roza opened space for the representation of subj ect women, which enter their bodies in their open-identity projects, scarching relentlessly for full satisfaction in the sexual and loving field, as more than "wanting-to-be," these women are imbued with the can-be". ven with the difficulties imposed by the inorgasmic body of Gilda and the aging body of Mary, both protagonists turn their eyes to their inland, leaving their concerns emerge through the narrative "voice" that was granted by the works of female authors, aiming, thus, the achievement of "pure relationships" that entangled love to sexuality.